Rapid bioprinting of conjunctival stem cell micro-constructs for subconjunctival ocular injection. (January 2021) - Zhong, Zheng; Deng, Xiaoqian; Wang, Pengrui; Yu, Claire; Kiratitanaporn, Wisarut; Wu, Xiaokang; Schimelman, Jacob; Tang, Min; Balayan, Alis; Yao, Emmie; Tian, Jing; Chen, Luwen; et al.
Abstract: Ocular surface diseases including conjunctival disorders are multifactorial progressive conditions that can severely affect vision and quality of life. In recent years, stem cell therapies based on conjunctival stem cells (CjSCs) have become a potential solution for treating ocular surface diseases. However, neither an efficient culture of CjSCs nor the development of a minimally invasive ocular surface CjSC transplantation therapy has been reported. Here, we developed a robust in vitro expansion method for primary rabbit-derived CjSCs and applied digital light processing (DLP)-based bioprinting to produce CjSC-loaded hydrogel micro-constructs for injectable delivery. Expansion medium containing small molecule cocktail generated fast dividing and highly homogenous CjSCs for more than 10 passages in feeder-free culture. Bioprinted hydrogel micro-constructs with tunable mechanical properties enabled the 3D culture of CjSCs while supporting viability, stem cell phenotype, and differentiation potency into conjunctival goblet cells. These hydrogel micro-constructs were well-suited for scalable dynamic suspension culture of CjSCs and were successfully delivered to the bulbar conjunctival epithelium via minimally invasive subconjunctival injection. This work integrates novel cell culture strategies with bioprinting to develop a clinically relevant injectable-delivery approach for CjSCs towards the stem cell therapies for the treatment of ocular surface diseases. Graphical abstract: Graphical Abstract. We present an integrated system that efficiently expanded CjSCs in vitro and utilized rapid bioprinting to fabricate hydrogel micro-constructs encapsulating CjSCs for subconjunctival injectable delivery to an ocular surface. Image 1